An investigation of effectiveness of classroom management strategies in a private school in the UAE: A case study at British International School Ajman - KHAN, MARIAM MAJEED (2018)
The purpose of my research is to investigate the existing classroom management strategies at British International School Ajman. The aim is to find out the problems teachers face while managing their classes. Through observation, it is understood that teachers who have good understanding and strong bond with their students are able to manage their classes effectively. Moreover, classroom rules, class routines, class environment, class seating arrangement and use of positive language also results in good classroom management. The teachers faced myriad problems while dealing with ADHD students. The school management must support teachers with extra workshops on dealing with behavioural problems in class.